Combining approximation and exact penalty in hierarchical programming. (3rd August 2022) - Bigi, Giancarlo; Lampariello, Lorenzo; Sagratella, Simone
Abstract : We address the minimization of an objective function over the solution set of a (non-parametric) lower-level variational inequality. This problem is a special instance of semi-infinite programs and encompasses, as particular cases, simple (smooth) bilevel and equilibrium selection problems. We resort to a suitable approximated version of the hierarchical problem. We show that this, on the one hand, does not perturb the original (exact) program 'too much', on the other hand, allows one to rely on some suitable exact penalty approaches whose convergence properties are established.